2018
DOI: 10.1007/s11557-018-1393-6
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Protohydnum (Auriculariales, Basidiomycota)

Abstract: Three species currently addressed to Protohydnum (Auriculariales) are studied with morphological and DNA methods. The genus Protohydnum is retained for the type species only, P. cartilagineum, recently re-collected in Brazil. The European species, P. piceicola, is not congeneric with P. cartilagineum and, therefore, placed in its own genus, Hyalodon, gen. nov. Another Hyalodon species, H. antui, is described from East Asia. The third member of Protohydnum sensu lato, P. sclerodontium from South-East Asia, is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…1). The genus Hyalodon is described in detail in Malysheva et al (2018), Mycostilla and Stypellopsis are introduced in Spirin et al (2019). The Heterochaetella species characterized by long, thick-walled, tubular cystidia are excluded from this study.…”
Section: Nrits + Nrlsu Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The genus Hyalodon is described in detail in Malysheva et al (2018), Mycostilla and Stypellopsis are introduced in Spirin et al (2019). The Heterochaetella species characterized by long, thick-walled, tubular cystidia are excluded from this study.…”
Section: Nrits + Nrlsu Datasetmentioning
confidence: 99%
“…This kind of basidium was first described by Wells (), but its taxonomic applicability has since then been judged in different ways (Donk , Reid , Wells 1994, Roberts ). Phylogenetic studies conducted over the last 20 years show that taxa with sphaeropedunculate basidia occur in several, rather distantly related lineages within Auriculariales (Weiss and Oberwinkler , Wells et al , Spirin et al , , Malysheva et al ). Weiss and Oberwinkler () assumed that the occurrence of this basidial type within a given lineage is constant and, therefore, taxonomically valuable.…”
Section: Introductionmentioning
confidence: 99%
“…taxa, and it is not closely related to the other poroid representatives of the order. While the latter ones (i.e., Aporpium, Elmerina, and Protodaedalea), as well as Protohydnum were rather extensively studied in the last years (Miettinen et al 2012, Zhou & Dai 2013, Sotome et al 2014, Vlasák et al 2016, Malysheva et al 2018, only a few new sequences were generated for Protomerulius and Heterochaetella, and therefore, their relationships stayed unresolved. In the present study, we revise generic and species-level taxonomy of Protomerulius and associated taxa, and provide new information about Heterochaetella cystidiophora Lowy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, molecular studies involving Heteroradulum have been carried out (Malysheva & Spirin 2017, Malysheva et al 2018, Yuan et al 2018. Phylogenetic study of the Auriculariales with stereoid basidiocarps revealed that Heteroradulum was validated and two new species, five combinations were introduced on the base of the combined data of the nuclear ribosomal LSU and the internal transcribed spacer (ITS) regions (Malysheva & Spirin 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic study of the Auriculariales with stereoid basidiocarps revealed that Heteroradulum was validated and two new species, five combinations were introduced on the base of the combined data of the nuclear ribosomal LSU and the internal transcribed spacer (ITS) regions (Malysheva & Spirin 2017). Malysheva et al (2018) revised of Protohydnum A. Möller (1895:173) and suggested that Heteroradulum grouped with Exidiopsis (Bref.)…”
Section: Introductionmentioning
confidence: 99%